Indices of granulocyte activity in inflammatory bowel disease. Issue 12 (December 1974) - Kane, S. P.; Hoffbrand, A. V.; Neale, G.
Abstract : In conditions with increased neutrophil production, the serum total vitamin B12 -binding capacity (TBBC) is considered to correlate with the blood pool size of neutrophil granulocytes. The serum lysozyme, on the other hand, is a measure of neutrophil (and monocyte) turnover. The mean serum TBBC was significantly raised in patients with ulcerative colitis (range 1.23-5.51 ng/ml; mean 2.64 ng/ml) and patients with Crohn's disease (range 1.58-9.29 ng/ml; mean 2.93 ng/ml). The elevated values were shown to be due to rises in the granulocyte-secreted binding proteins, transcobalamins I and III. The TBBC was shown to rise with increasing activity of disease and to correlate roughly with the blood neutrophil granulocyte count. Patients with inflammatory bowel disease also had a significantly raised mean level of serum lysozyme (range 3.1 to 10.4 μg/ml; mean 6.8 μg/ml), but there was no correlation in individual patients between serum lysozyme and total B12 -binding capacity. These results are taken to indicate an enlarged granulocyte pool and increased granulocyte turnover in inflammatory bowel disease.